(untitled) (Revista Internacional de Folkcomunicação, 2019)
This article aims to analyze the images linked in the main page of the website of the International Cooperation Agency of the Institute of Man and Environment in the Amazon (IMAZON). In which one inquires whether the images of the Amazon, contained in the main page, are relevant for the construction and / or maintenance of the Amazonian imaginary, from its representations. Having as methodological process support the discourse analysis of Charaudeau (2008), thus identifying the expressive elements that characterize Amazonia in the images. Establishing a symbolic construction, on the region, presenting elements and constructive values, for the construction of the Amazonian imaginary. Image; Speech; Amazon; International cooperation.